Ethical Dimension of Human Identity in the Light of Chosen Narrative Approaches - Ziółkowska-Juś, Anna (Sensus Historiae, 2020)
The aim of the article is to analyse the relationship between ethics and human identity in Alasdaire MacIntyre’s, Charles Taylor’s and Paul Ricoeur’s narrative approaches.These concepts show that ethics and constitution of human identity condition each other. The article shows the specificity of ethics (emerging from narrative concepts) which contains both aspects of modern and post-modern ethics and at the same time goes beyond their one-sidedness and limitations.